2021
DOI: 10.1002/sia.7011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on microstructure, mechanical, and tribological property of gamma‐irradiated polytetrafluoroethylene, polyetheretherketone, and polyimide polymers

Abstract: In this paper, three commercial polymers (polytetrafluoroethylene [PTFE], polyetheretherketone [PEEK], and polyimide [PI]) were irradiated by gamma rays in the ambient air. The changes in microstructure, mechanical, and tribological properties of these three polymers after irradiation were investigated comparatively. The results display that both the surface and internal structures of PTFE are degraded due to the irradiation chemical reaction, and the molecular chain scission at the surface is more severe than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…The slight reduction of O concentration was attributed to the short exposure time in the air environment. The samples are not sufficiently oxidized relative to the original sample surface, resulting in a decrease in oxygen content [28] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slight reduction of O concentration was attributed to the short exposure time in the air environment. The samples are not sufficiently oxidized relative to the original sample surface, resulting in a decrease in oxygen content [28] …”
Section: Resultsmentioning
confidence: 99%
“…The samples are not sufficiently oxidized relative to the original sample surface, resulting in a decrease in oxygen content. [28] To reveal the possible chemical reaction occurring on three polymers during the gamma irradiation process, the C 1s XPS spectra of the pristine, the irradiated PEKÀ C, PEKÀ P and PEKÀ F were further analyzed. For the PEKÀ C before and after irradiation, the peaks of C 1s can be deconvoluted into four peaks at near 284.8, 286.5, 287.3 and 289 eV, corresponding to CÀ C, CÀ O, C=O and OÀ C=O bonds, respectively.…”
Section: Chemistryselectmentioning
confidence: 99%
“…Numerous researches have examined how PEEK and its composites react to various radiation sources, such as heavy ions [ 12 , 13 , 14 ], gamma rays [ 15 , 16 ], UV radiation [ 17 ], or combined with aging [ 18 ] and electron irradiation [ 19 , 20 ] since the polymer was first commercialized in 1978. These methods are very effective for controlling various properties of materials including polymers.…”
Section: Introductionmentioning
confidence: 99%
“…32 Conventionally, irradiation treatment technology which bears the advantages of cleanliness and high efficiency has been widely adopted in industrial sectors to modify the properties of polymer substrates, especially in terms of PTFE. [33][34][35][36] Kamga et al 37 prepared polyamide (PA)-based composites which were modified using irradiation treated PTFE. The results indicated that using irradiation treated PTFE as solid lubricant resulted in lower friction coefficient and wear rate.…”
Section: Introductionmentioning
confidence: 99%